Increase in optimal configuration of 25–60-day atmospheric circulations for Yangtze heavy rainfall under global warming background - Jianying Li; Yang Chen; Jiangyu Mao; Panmao Zhai (Weather and Climate Extremes, 2023)
In summer, the middle and lower reaches of the Yangtze River (MLYR) often suffers from severe floods as a result of a dominant intraseasonal oscillation (ISO) of rainfall with the quasi-period of 25–60 days. 75% of flooding events during summers of 1961–2022 are found to occur following wet phases of the 25−60-day ISO in rainfall. This study objectively extracts the optimal configuration (OC) of 25−60-day atmospheric ISOs for the wet phase of MLYR rainfall. The OC is characterized by the quadruple pattern of tropical convection configuring with the 25−60-day Silk Road Pattern (SRP) in the mid−high latitudes. The 25−60-day SRP in cooperation with tropical ISO over the western Pacific induces dipolar vertical cells over eastern China, with ascending branch between the vertical cells providing the vitally dynamical condition for MLYR rainfall. With topographic blocking of the Tibetan Plateau, the northward-propagating tropical ISO over the Indian Ocean enhances maintenance of the 25−60-day SRP via upper-tropospheric divergent flows, thus anchoring anomalous ascents to the MLYR. Numerical experiments further verify the remarkable tropical-extratropical interaction around the Tibetan Plateau in this OC. Under the global warming background, the tropical 25−60-day ISO tends to strengthen, leading to an increase in the occurrence frequency of strong OC through tropical-extratropical interaction, and thus the severe flood events doubled in summers of 1991–2020.